STRATEGI PENINGKATAN PENDAPATAN NELAYAN SKALA KECIL BERKELANJUTAN MELALUI PEMANFAATAN POTENSI GURITA (Octopussp) DI KABUPATEN SIMEULUE PROPINSI ACEH - Amarullah, Teuku; Zuaridah, Syarifah; Gazali, Mohamad (Universitas Teuku Umar, 2020)
Simeulue Islands are the farthest area in West Indonesia that have potency in fisheries and marine science sectors. One of the marine resources from Simeulue Island are Octopus. The octopus price in the market were prospective than other fisheries commudity. However, we have no strategy to increase the Octopus sustainability. Thus, the research about the socio-economic were very important. The aim of this research was to determine the increasing strategy of small scale fishermen sustainability through the utilization of Octopus potency at Simeulue Island. The research method by using descriptive method with sampling method that used accidental sampling. Subsequently, those samples were analysed by using SWOT Analysis. The result showed that the internal factor in our study are togertherness in capture operational system with value as much as 0,58. Moreover, the weakness generated the lack attention from institutional as much as 0,31. In external factors showed the opportunity from fisheries resources abundantly as much as 0,61. However, the threats showed mostly local fishermen catch the fisheries resources by using unfriendly fishing gear. According to the scoring I grand matrix of small scale fisheries in Simeulue Islands. Thus, this grand strategy in the first kuadran. It means that the small scale fisheries have high opportunity for developing with utilize the strength and grab the opportunity. Keywords :small scale, fisheries, octopus, Simeulue